DAMPAK KONVERSI LAHAN PERTANIAN KE NON-PERTANIAN TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI KECAMATAN CIBADAK KABUPATEN SUKABUMI - Hatta, A.; Warlina, Lia (Universitas Komputer Indonesia (UNIKOM), 2019)
ABSTRAK The research objective were to identify land use change in Kecamatan Cibadak and to describe the impact of land use change toward farmer’s income. This research used primary and secondary data. Primary data was collected by distribution of questionary, while secondary data was obtained from related intitutions.overlay technique was used to identify land use change. In other hand, descriptive analysis was use to describe land use change impact toward on farmer’s income. The total change of land use was 1,86 % in seven years (2006-2013). The total change of land use was 1,19 % in three years (2013-2016). The total income of land use type settlement was 33,112 ha in the ten years. However, the total change of agricultural land was 19,699 ha. It were 11 farmers who convert their land stated that theor income were in change deu to land conversion. Their agricultural land was converted into built area. The farmers still own the land and the culding or houses. Kata Kunci : Guna Lahan, Perubahan Guna Lahan, Pemasukan